Students' misconceptions on the concept of sound: a case study about Marinyo, Tanimbar Islands - Batlolona, John Rafafy; Jamaludin, Jamaludin (Intelektual Pustaka Media Utama, 2024)
Marinyo is a culture left by the Portuguese around the 15th century in Maluku. The purpose of this study was to find out to what extent students' misconceptions about the concept of sound in the Marinyo case in the Kepuluan Tanimbar Regency. The method used was a qualitative study in ethnography in ten villages in two sub-districts. In addition, they conducted a survey in the form of a diagnostic test in the form of questions related to the Marinyo case on 300 elementary school students. The findings in the field show that students experience relatively high misconceptions. It was because teachers did not accustom students to learn from natural phenomena around them and were given scientific questions to seek, find and provide answers and solutions related to these natural phenomena. The teacher was more pursuing the conditions and problems of physics in textbooks and less exploring contextual matters. Future researchers are suggested to develop physics or science teaching materials based on regional local advantages that are oriented towards understanding concepts, mental models, critical thinking, problem-solving, creativity and innovative thinking so that teachers and students can learn well so that knowledge of science becomes better.